PENGARUH ELECTRONIC WORD OF MOUTH, KESESUAIAN HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN - Putri, Putu Dian Delicia Undiani; Bayu Rahanatha, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
Purchasing decision is a final decision or choice that consumers have to buy products or use services with various considerations. This study aims to explain the effect of electronic word of mouth, price compitability and service quality on purchasing decisions for consumers of Kytha Coffee in Denpasar City. The number of samples used was 140 respondents and they had made purchases at Kytha Coffee in Denpasar City. The sampling method used in this research is non-probability sampling with accidental sampling technique. Data collection was obtained from the results of distributing questionnaires using the Google form as a research instrument. The results of multiple linear regression analysis show that the variables electronic word of mouth, price compitability and service quality have a positive and significant effect on purchasing decisions. The results of this study indicate that the higher the electronic word of mouth, the purchasing decision will increase, as well as the compitability of price and service quality, the better it will increase purchasing decisions.